Reverse genetics construction and pathogenicity of a novel recombinant NADC30-like PRRSV isolated in China - Guo, Jinyao; Li, Chenxi; Lu, Huipeng; Wang, Bin; Zhang, Linjie; Ding, Jingjing; Jiao, Xue; Li, Qingyu; Zhu, Shanyuan; Wang, Anping; Li, Yanhua (Frontiers in Veterinary Science, 2024)
China has the largest pig herd in the world which accounts for more than 50% of the global pig population. Over the past three decades, the porcine reproductive and respiratory syndrome virus (PRRSV) has caused significant economic loss to the Chinese swine industry. Currently, the prevalent PRRSV strains in the field are extremely complicated, and the NADC30-like strains, NADC34-like strains, and novel recombinant viruses have become a great concern to PRRS control in China. In this study, a novel NADC30-like PRRSV, named GS2022, was isolated from the lung of a dead pig collected from a farm that experienced a PRRS outbreak. The complete genome of GS2022 shares the highest identity with the NADC30 strain and contains a discontinuous deletion of 131 aa in nsp2. Novel deletion and insertion have been identified in ORF7 and 3'UTR. Recombination analysis revealed that the GS2022 is a potential recombinant of NADC30-like and JXA1-like strains. Both inter-lineage and intra-lineage recombination events were predicted to be involved in the generation of the GS2022. An infectious cDNA clone of GS2022 was assembled to generate the isogenic GS2022 (rGS2022). The growth kinetics of rGS2022 were almost identical to those of GS2022. The pathogenicity of the GS2022 and rGS2022 was evaluated using a nursery piglet model. In the infection groups, the piglets exhibited mild clinical symptoms, including short periods of fever and respiratory diseases. Both gross lesions and histopathological lesions were observed in the lungs and lymph nodes of the infected piglets. Therefore, we reported a novel recombinant NADC30-like PRRSV strain with moderate pathogenicity in piglets. These results provide new information on the genomic characteristics and pathogenicity of the NADC30-like PRRSV in China.